PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA SMA KELAS X PADA MATERI GERAK LURUS - Rika Nurbadiah; Yennita Yennita; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aimed to determine differences in students physics problem solving abilities between classes applying the problem posing learning model and the class applying conventional learning. The kind of research use is was quasy experiment with Two-Group Posttest-Only Design. The subject of study is learners class X MIPA Senior High School 12 Pekanbaru academic year 2018 /2019, consisting of class X MIPA.2, Was a class the experiments were 35 students and class X MIPA.3 as a class control by 35 students. The research instruments used is about a test questions to solve physics problems. Data collection technique in this research by giving a test of the ability to solve physics problems after learning held on the class. The data is analysed in descriptive to see the results of students problem solving ability scores and analysed in inferential using the T test. The results showed that there are significant differences between the students physics problem solving abilities in the learning class and the problem posing learning model with the conventional class of straight-motion material. The average score of students physics problem solving ability of students who learn with problem posing models is higher than conventional learning..Key Words: Problem Posing, Problem Solving Ability, Straight Motion